1999
DOI: 10.1515/cclm.1999.002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Troponin I and Troponin T: Recent Players in the Field of Myocardial Markers

Abstract: The troponin (Tn) complex consists of three subunits referred to as TnT, TnI and TnC. Myocardium contains TnT and TnI isoforms which are not present in skeletal muscles and which can be separated from the muscular isoforms by immunological techniques. Using commercially available immunoassays, clinical laboratories are able to determine cardiac TnT and TnI (cTnT and cTnI) quickly and reliably as classical cardiac markers. After acute myocardial infarction, cTnT and cTnI concentrations start to increase in seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
29
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 88 publications
0
29
0
2
Order By: Relevance
“…TnI is the inhibitory subunit that can bind to actin-tropomyosin and prevent muscle contraction by inhibition of actin-activated myosin (actomyosin) ATPase activity (33). TnI has received considerable attention as a serum biomarker of myocardial tissue damages (2,31) and as a key phosphoprotein that regulates cardiac contractile function (13,40). Its role in mediating cardiac dysfunction in humans and experimental animals is controversial and continues to be actively investigated.…”
mentioning
confidence: 99%
“…TnI is the inhibitory subunit that can bind to actin-tropomyosin and prevent muscle contraction by inhibition of actin-activated myosin (actomyosin) ATPase activity (33). TnI has received considerable attention as a serum biomarker of myocardial tissue damages (2,31) and as a key phosphoprotein that regulates cardiac contractile function (13,40). Its role in mediating cardiac dysfunction in humans and experimental animals is controversial and continues to be actively investigated.…”
mentioning
confidence: 99%
“…Key Words: troponin Ⅲ myocardial infarction Ⅲ biological markers Ⅲ diagnosis Ⅲ blotting, western I t is widely accepted that the presence of cardiac troponin I or T (cTnI or cTnT) in blood serum indicates myocardial damage; thus, cTnI and cTnT are considered specific biochemical markers for acute myocardial infarction (AMI). [1][2][3] Despite the widespread use of cTnI and cTnT detection as a diagnostic tool in acute coronary syndromes, problems arise from variations in the sensitivity, selectivity, and specificity of various commercially available diagnostic cTnI immunoassay kits. 4 -7 These differences are due to (1) the lack of mass standardization, 8 -10 (2) the presence of post-translationally modified cTnI in the serum, and (3) variations in antibody cross-reactivities to the various detectable forms of cTnI.…”
mentioning
confidence: 99%
“…[1][2][3] Despite the widespread use of cTnI and cTnT detection as a diagnostic tool in acute coronary syndromes, problems arise from variations in the sensitivity, selectivity, and specificity of various commercially available diagnostic cTnI immunoassay kits. 4 -7 These differences are due to (1) the lack of mass standardization, 8 -10 (2) the presence of post-translationally modified cTnI in the serum, and (3) variations in antibody cross-reactivities to the various detectable forms of cTnI.…”
mentioning
confidence: 99%
“…5 It has been observed that this structural cell protein may be detected in the blood of patients with acute coronary syndrome, 6 after coronary angioplasty, 7 in heart failure, 8 acute myocarditis, 9 and other clinical situations in which conventional markers of myocyte necrosis are often negative. Thus, the new concept of 'minor myocardial damage' has emerged.…”
mentioning
confidence: 99%